Tungsten-Modulated Molybdenum Selenide/Graphene Heterostructure as an Advanced Electrode for All-Solid-State Supercapacitors - Qixian Liu; Jing Ning; Haibin Guo; Maoyang Xia; Boyu Wang; Xin Feng; Dong Wang; Jincheng Zhang; Yue Hao (Nanomaterials, 2021)
Transition metal dichalcogenides (TMDs) have attracted widespread attention due to their excellent electrochemical and catalytic properties. In this work, a tungsten (W)-modulated molybdenum selenide (MoSe2)/graphene heterostructure was investigated for application in electrochemistry. MoSe2/graphene heterojunctions with low-doped W compositions were synthesized by a one-step hydrothermal catalysis approach. Based on the conducted density functional theory (DFT) calculations, it was determined that inserting a small amount of W (≈5%) into the MoSe2/graphene heterostructure resulted in the modification of its lattice structure. Additionally, an increase in the distance between layers (≈8%) and a decrease in the adsorption energy of the potassium ions (K+) (≈−1.08 eV) were observed following W doping. Overall, the electrochemical performance of the MoSe2/graphene hybrid was enhanced by the presence of W. An all-solid-state supercapacitor device prepared using electrodes based on the W-doped MoSe2/graphene composite achieved excellent capacitance of 444.4 mF cm−2 at 1 mV s−1. The results obtained herein revealed that the MoSe2/graphene hybrid exhibiting low W composition could be valuable in the field of energy storage and isoelectronic doping of TMDs.